Short notes on the civil services (clarification ,control and appeal) rules 1930,Along with allied rules as applicable in U.P - Kamlesh Singh (U.P, 1984)
The Civil Services (Classification, Control and Appeal) Rules 1930 along with allied rules as applicable in Uttar Pradesh, have assumed great importance as favouritism, castism and interpretations of service rules in favour of their arbitrary actions by the employer on the one hand and trade Unionism and consciousness of their rights without care for their corresponding duties by the employees on the other hand, have given rise to a lot of litigations between the two. This tremendous rise in litigation compelld the State Government to pass the U. P. Public Services Tribunal Act of 1976 (U. P. Act No. XVII of 1976) to lessen the burden of the High Court Still the tribunals and High Court are overburdened with cases. This proves undoubtedly the continuous rise of litigation between the employer and employee.
Keywords: Civil service -Rules regulation etc